2009
DOI: 10.1248/bpb.32.1584
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Taurine, a Novel Biochemical Modulator, on the Antitumor Activity of Doxorubicin

Abstract: In cancer therapy, novel chemotherapeutic agents are being developed continually, 1) however, cancer-induced lethality is still high in many countries because of recalcitrant tumors and the appearance of resistant tumors. Furthermore, adverse reactions by antitumor drugs not only inhibit the therapeutic index but also require the use of combined agents to decrease these adverse reactions and the quality of life (QOL) of patients can worsen. While the development of novel antitumor drugs is a long and costly pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…It has been reported that Tau has an efficacy-enhancing and toxicity-reducing effect on cyclophosphamide [22] and improve the efficacy of cyclophosphamide in the treatment of leukemia [23]. Tau can improve the anti-tumor efficacy of doxorubicin without increasing the side effects [24]. (ii) Tau inhibits cancer growth by improving the antioxidant capacity in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that Tau has an efficacy-enhancing and toxicity-reducing effect on cyclophosphamide [22] and improve the efficacy of cyclophosphamide in the treatment of leukemia [23]. Tau can improve the anti-tumor efficacy of doxorubicin without increasing the side effects [24]. (ii) Tau inhibits cancer growth by improving the antioxidant capacity in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a lot of researches through light on the use of taurilidine as antineoplastic drug in human bladder carcinoma [49] gastro-intestinal cancer [50] to prevent the development of lung metastasis [51], and it may offer additional therapeutic option in patient with colon adenocarcinoma [51], as a useful modulator to enhance the therapeutic index of some antitumor agents [16], in the treatment of oesophageal cancer [14], in treatment of malignant mesothelioma [52] and as a biomarker in non-muscle invasive bladder cancer [53]. In conclusion and based on the present study we can strongly suggest the assessment of taurine level in sera of patients with high risk of breast cancer and in the early diagnosis of any malignant changes in the breast.…”
Section: Discussionmentioning
confidence: 99%
“…Taurine and its derivatives such as taurolidine and taurochloramin were found to display antineoplastic effect both in vitro and in vivo; through suppressing cell proliferation, enhancement of tumor cell apoptosis [14][15][16][17][18][19][20][21], and through an antiangiogenic effects [15,22] while enhancing the therapeutic index of some antitumer agent [16]. Recently taurine level used as early marker in hepatocellular carcinoma (HCC) [17] and in cancer uterus [18].…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we reported improved DOX-induced antitumor activity using the food components caffeine, theanine, and cucurbitacins. [6][7][8][9][10][11][12][13][14][15] It appeared that these effects were mediated by increased DOX concentration in the tumors, which suppress DOX efflux from tumor cells. In contrast, linalool promoted DOX influx into tumor cells and enhanced its activity by acting on the Na + -dependent nucleoside transporter (CNT) 3.…”
mentioning
confidence: 99%